2018
DOI: 10.1093/femsle/fny031
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in anammox processes for wastewater nitrogen removal: recent advances and future prospects

Abstract: The discovering of anaerobic ammonium oxidation (anammox) process led to the development of autotrophic nitrogen removal systems for the treatment of effluents with low C:N rate. The anammox processes provide an efficient way to remove high concentrations of ammonium compounds from industrial and urban wastewater and covert them to dinitrogen. Nevertheless, recently obtained results suggest new ways for research on autotrophic nitrogen removal system including possibility for low temperature operation, adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…The high environmental sensitivity of AnAOB brings many obstacles to mainstream application. Researchers have discovered that the operational parameters (temperature, dissolved oxygen, pH), organics, antibiotics, salts, heavy metals, and even excess ammonia and nitrite have certain adverse effects on the growth and activity of AnAOB (Gonzalez‐Martinez, Muñoz‐Palazon, Rodriguez‐Sanchez, & Gonzalez‐Lopez, 2018; Nsenga Kumwimba, Lotti, Şenel, Li, & Suanon, 2020). Nitrogen is mainly present in the form of ammonium in raw municipal wastewater, and nitrite is strictly limited.…”
Section: Crucial Factors For the Stable Operation Of Anammox Bioreactmentioning
confidence: 99%
“…The high environmental sensitivity of AnAOB brings many obstacles to mainstream application. Researchers have discovered that the operational parameters (temperature, dissolved oxygen, pH), organics, antibiotics, salts, heavy metals, and even excess ammonia and nitrite have certain adverse effects on the growth and activity of AnAOB (Gonzalez‐Martinez, Muñoz‐Palazon, Rodriguez‐Sanchez, & Gonzalez‐Lopez, 2018; Nsenga Kumwimba, Lotti, Şenel, Li, & Suanon, 2020). Nitrogen is mainly present in the form of ammonium in raw municipal wastewater, and nitrite is strictly limited.…”
Section: Crucial Factors For the Stable Operation Of Anammox Bioreactmentioning
confidence: 99%
“…Therefore, controlling pH closely coordinates the efficiency of nitrogen removal of anammox reactors. The implementation of anammox in a single bioreactor is a novel approach that can remove the nitrogen from both municipal and industrial wastewaters by controlling pH and dissolved oxygen through aeration [33,77]. The single-stage anammox process can achieve an energy-cost saving of 25% compared to the conventional process provided that stability of pH and aeration is controlled [59,77].…”
Section: Phmentioning
confidence: 99%
“…This suggested that the application of anammox in an environment with moderate DO level in the presence of symbiont bacteria could be considered. Controlling the DO levels in the reactor would support the oxidation of ammonium to nitrite and prevent the oxidation of nitrite to nitrate, which is challenging for the anammox reaction [77,87].…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 99%
See 2 more Smart Citations